PELATIHAN BRANDING DAN DESAIN PACKAGING UNTUK PRODUK PAKAN TERNAK UMKM MAKMUR DUA PUTRI DESA JATIKALANG KRIAN SIDOARJO - Utomo, Yitno; Yunia Dwie Nurcahyanie; Djoko Adi Walujo; Nushron Ali Mukhtar; Rusdiyantoro (Kanigara, 2024)
The implementation of assistance for UMKM Makmur Dua Putri towards business development and professionalism was chosen using Branding and Packaging steps. The branding logo of the letters "MDP" is an abbreviation or acronym for Makmur Dua Putri, the dominant letter "M" with the cutting of the next two letters, namely "DP", is the concept that "Makmur" is the goal of this business. Of course, for every business, the goal of its vision and mission is prosperity. The text at the bottom "Prosperous Two Daughters" emphasizes the meaning, namely to interpret the good fortune of the trust given by God to two daughters. The choice of green is synonymous with coolness or returning to nature. This branding emphasizes that the animal feed made is made from ingredients that are returned to nature and are environmentally friendly. After obtaining the brand name and packaging, the animal feed business in Jatikalang village, Krian subdistrict, Sidoarjo district, will develop the marketing process outside Java.